Antimicrobial activity of an Algerian medicinal plant: Carthamus caeruleus L. - Ghosh, Kavisa (Pharmacognosy Communications)
Aims: The aim of the present study was to evaluate the anticancer effect of lemongrass oil and citral emulsion on cervical cancer cell lines (HeLa and ME-180) in vitro. Settings and Design: Citral is a very important component in lemongrass oil. It is proved to have anticancer properties in various human cancer cell lines. Methods and Material: DLS analysis revealed the average size of the lemongrass oil emulsion to be 267 nm and the average size of the citral emulsion to be 270 nm. The anticancer effect of both the emulsions was determined by MTT assay, DCFH-DA method, Rh-123 and AO/EtBr-staining. Statistical analysis used: One-way ANOVA followed by DMRT taking p<0.05 to test the significant difference between groups. Results: The results summarize that lemongrass oil and citral emulsions initiate the cancer cell death by decreasing cell proliferation, increasing intracellular ROS, altering mitochondrial membrane potential, and initiating apoptosis in HeLa and ME-180 cell lines. The present findings of this study clearly demonstrate the involvement of oxidative mechanism for the anti-proliferative effect in HeLa and ME-180 cell lines. ME-180 being chemosensitive showed good results at lower concentrations of citral (IC50 24 h 300 μg/ml), as compared to chemoresistant HeLa cells (citral IC50 24 h 500 μg/ml). Whereas lemongrass oil exhibited better activity in both the cell lines (IC50 24 h 200 μg/ml). Conclusions: All the results suggest lemongrass oil and citral emulsion could be considered as potent candidates for anticancer agents.
Keywords: Lemongrass oil; Citral; Emulsion; Anticancer; HeLa; ME-180